2013
DOI: 10.1093/mnras/stt686
|View full text |Cite
|
Sign up to set email alerts
|

Analytical solutions to the mass-anisotropy degeneracy with higher order Jeans analysis: a general method

Abstract: The Jeans analysis is often used to infer the total density of a system by relating the velocity moments of an observable tracer population to the underlying gravitational potential. This technique has recently been applied in the search for Dark Matter in objects such as dwarf spheroidal galaxies where the presence of Dark Matter is inferred via stellar velocities. A precise account of the density is needed to constrain the expected gamma ray flux from DM self-annihilation and to distinguish between cold and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 51 publications
0
43
0
Order By: Relevance
“…2, where all slopes γ ∈ [0, 1] are allowed at the 95% level). The difficulty to constrain this slope is generally attributed to the degeneracy of the DM parameters with the anisotropy parameter βani(r), and methods relying on higher order of the Jeans analysis have been proposed to circumvent this issue (Richardson & Fairbairn 2013. See also the MAMPOSSt approach in Mamon et al (2013).…”
Section: Preliminary Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2, where all slopes γ ∈ [0, 1] are allowed at the 95% level). The difficulty to constrain this slope is generally attributed to the degeneracy of the DM parameters with the anisotropy parameter βani(r), and methods relying on higher order of the Jeans analysis have been proposed to circumvent this issue (Richardson & Fairbairn 2013. See also the MAMPOSSt approach in Mamon et al (2013).…”
Section: Preliminary Discussionmentioning
confidence: 99%
“…The main source of uncertainty in this ideal case is the velocity anisotropy profile. Higher-order Jeans analyses will probably appear as very helpful tools for reducing these uncertainties (see e.g., Richardson & Fairbairn 2013. However, we have found that even in the context of a maximum knowledge analysis (i.e., with the light profile and velocity anisotropy perfectly known), the best that can be achieved is J ±95% CI /J median 1.5 at αint = αc, and 2.5 at 0.1 αc and 10 αc.…”
Section: Conclusion For the Different Sample Sizesmentioning
confidence: 99%
“…In the literature, one can find other approaches to lift the mass/anisotropy degeneracy, for example, by fitting the LOS velocity kurtosis profiles together with the LOS velocity dispersion profiles (Łokas 2003;Łokas & Mamon 2003;Richardson & Fairbairn 2013).…”
Section: Dynamical Modelsmentioning
confidence: 99%
“…Since using higher order moments might reduce the degeneracy between the velocity anisotropy and the mass profile (e.g. Merrifield & Kent 1990;Richardson & Fairbairn 2013) we choose to use four velocity moments. We do not use higher moments since these are observationally harder to constrain.…”
Section: Fitting Orbital Weightsmentioning
confidence: 99%